Siliques Are Red1 from Arabidopsis acts as a bidirectional amino acid transporter that is crucial for the amino acid homeostasis of siliques - Ladwig, Friederike; Stahl, Mark; Ludewig, Uwe; Hirner, Axel A.; Hammes, Ulrich; Stadler, Ruth; Harter, Klaus; Koch, Wolfgang (Plant Physiology, 2012)
Many membrane proteins are involved in the transport of nutrients in plants. While the import of amino acids into plant cells is, in principle, well understood, their export has been insufficiently described. Here, we present the identification and characterization of the membrane protein Siliques Are Red1 (SIAR1) from Arabidopsis (Arabidopsis thaliana) that is able to translocate amino acids bidirectionally into as well as out of the cell. Analyses in yeast and oocytes suggest a SIAR1-mediated export of amino acids. In Arabidopsis, SIAR1 localizes to the plasma membrane and is expressed in the vascular tissue, in the pericycle, in stamen, and in the chalazal seed coat of ovules and developing seeds. Mutant alleles of SIAR1 accumulate anthocyanins as a symptom of reduced amino acid content in the early stages of silique development. Our data demonstrate that the SIAR1-mediated export of amino acids plays an important role in organic nitrogen allocation and particularly in amino acid homeostasis in developing siliques. © 2012 American Society of Plant Biologists. All Rights Reserved.